Resistance to first‐generation somatostatin receptor ligands does not impair the results of gamma knife radiosurgery in acromegaly. (4th July 2021) - Losa, Marco; Resmini, Eugenia; Barzaghi, Lina R.; Albano, Luigi; Bailo, Michele; Webb, Susan M.; Mortini, Pietro
Abstract: Objective: Gamma knife radiosurgery (GKRS) has proven to be an effective adjuvant treatment for patients with acromegaly. We performed the present study to investigate, which would be the outcome of GKRS, independently on the response to somatostatin receptor ligand (SRL). Design: Retrospective, observational study. Patients: Ninety‐six patients with active acromegaly were included. Measurements: The cumulative probability of normalisation of insulin‐like growth factor 1 (IGF‐1) levels after GKRS was assessed by the Kaplan–Meier method. The association of several clinical characteristics with GKRS outcomes was explored with the use of a Cox proportional‐hazard model with the relative hazard ratio and 95% confidence interval (CI). Results: Resistance to SRL occurred in 39 of the 96 patients (40.6%). After GKRS, patients resistant to SRL had a 5‐ and 10‐year probability of remission of 40.7% (95% CI: 23.7%–57.7%) and 75.9% (95% CI: 57.9%–93.9%), respectively. Patients responding to SRL had a 5‐ and 10‐year probability of remission of 46.8% (95% CI: 32.2%–61.4%) and 58.1% (95% CI: 41.5%–74.7%), respectively. The difference was not significant ( p = .48 by the log‐rank test). Multivariate Cox analysis confirmed that the only independent variables associated with GKRS outcome were basal growth hormone (GH; p = .001) and IGF‐1 multiple of the upper limit of normal levels before GKRS ( p = .013). Conclusion: We demonstrate for the first time that the responsiveness to SRL has no effect on the probability to obtain remission of acromegaly after GKRS. The remission of disease occurred more frequently in patients who had lower GH and IGF‐1 levels before GKRS.